Women can transfer their ability to cope with stress from sport to academic contexts - Guzman, J. F.; Carratala, H. (European Journal of Human Movement, 2023)
This study retrospectively examined 182 high school student-athlete women aged 13-18 using Fletcher and colleagues' (2005, 2006) stress, emotion, and performance model to evaluate the impact of coping on engagement in both sports and academic settings. Additionally, the transfer of coping from sport to study was studied, with sports task-oriented coping acting as a moderator. Results indicated that in sports, stress was positively associated with emotional coping and negatively with engagement, and task-oriented coping positively with engagement. In the academic setting, stress was positively correlated with distancing coping, and task-oriented coping positively with engagement. Emotional coping and task-oriented coping both served as mediators, and sports task-oriented coping moderated academic stress and task-oriented coping. The findings support the processual model of stress and suggest that task-oriented coping should be encouraged and emotion-oriented coping should be avoided in both sports and academic settings. Furthermore, sport task-oriented coping was shown to transfer to the academic setting, as academic task-oriented coping decreased when sport task-oriented coping was below a certain threshold. Thus, it may be concluded that coping is a life skill that facilitates engagement in activities and may be transferred from sport to study in this sample of female student-athletes.